How agile coaches create an agile mindset in development teams: Insights from an interview study. Issue 12 (19th July 2022) - Klünder, Jil; Trommer, Felix; Prenner, Nils
Abstract: Since the publication of the agile manifesto in 2001, many companies implement an agile—or at least more agile—software development process. However, only including agile methods or practices in the overall process does not guarantee being agile. The mindset of the people involved in the process, including the development team, the customers, and the management, is of particular importance. As such an agile mindset cannot be enforced, the process of creating a suitable mindset needs to be handled with care. In an interview study with nine agile coaches, we analyzed which aspects they perceive being of particular importance during an agile transformation. One of these aspects is the agile mindset. We figure out how they support the creation of such a mindset. We identify 12 categories related to the process of creating an agile mindset. These categories include the collaboration between the coach and the management as well as the necessity to internalize the agile values. The main factor for succeeding with the creation of an agile mindset, however, can be hardly influenced: The success strongly depends on the personal prerequisites and attitudes of the individuals involved in the process, mainly the development team. We synthesize the results of our study into a timeline describing the process of how an agile coach can support the development team creating an agile mindset as part of the transformation towards an agile development process. Abstract : Creating an agile mindset during a transformation is important but very difficult. In an interview study with nine agile coaches, we analyze how they handle this difficulty and what they do to support the teams during this process. They identify personal prerequisites and attitudes being most important for succeeding with the mindset creation.